Analysis of Mathematics Learning Difficulties in Addition and Subtraction Material in Grade II Elementary School - Haliza, Risma; Indah Sari, Arissona Dia (Jurnal Elementaria Edukasia, 2025)
This study aims to identify the obstacles faced by grade II elementary school students in learning addition and subtraction material. This study uses a qualitative approach with a descriptive method, which was carried out in May 2024. Data were collected through observation, interviews, and documentation, then analyzed using the Milles and Huberman interactive analysis method which includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that there are internal factors, namely health conditions and physical disabilities that affect mathematical understanding, low motivation and little interest can hinder mathematical understanding, and external factors such as parental attention, school facilities, community environment, and learning strategies that affect the effectiveness of mathematics learning. This study also found that collaboration between teachers and parents is very important in uniting student learning progress and overcoming the difficulties faced. It is recommended that there be increased assistance in learning basic mathematical operations by educators or parents, as well as the use of questions that are appropriate to the student's learning stage using concrete media and parental involvement in improving mathematics learning skills. Keywords: Addition and Subtraction, Learning Feasibility, Mathematics